Case Report of Cutaneous Squamous Cell Carcinoma at the Wrist Joint and the Public Health Crisis of Arsenicosis - Sachan, Sonal (J Health Pollut, 2021)
CONTEXT. Arsenicosis is caused by long term (6 months plus) ingestion of arsenic above a safe dose, characterized by skin lesions and possible involvement of internal organs. Arsenicosis is common in India and Bangladesh where naturally occurring high concentrations of arsenic in the earth's crust contaminate ground water, causing adverse health effects. CASE PRESENTATION. We report a case of a 55-year-old Indian male, resident of a known arsenic endemic region of Uttar Pradesh who suffered from characteristic pulmonary and cutaneous features of chronic arsenic toxicity which included radiological findings of interstitial lung disease, hyperkeratotic lesions over the palms and soles, rain drop like pigmentation over the trunk, and carcinomatous changes at the wrist joint. The patient was started on chelating agents (d-penicillamine) and oral retinoids (isotretinoin) followed by the surgical excision of the carcinoma. DISCUSSION. Environmental contamination with arsenic is a well-known health hazard in South Asian countries. The main source is consumption of contaminated ground water for domestic purposes. Cutaneous lesions, internal organ involvement including interstitial lung disease and carcinomas as observed in our patient have been reported in the literature. Various mechanisms like epigenetic changes and arsenic-induced immune suppression have been proposed for the development of cutaneous carcinomas with prolonged exposure to arsenic. RELEVANCE TO CLINICAL PRACTICE. Among the various causes of palmo-plantar hyperkeratosis, arsenicosis should be kept in mind when presenting in combination with pigmentary changes and carcinomatous growth from an arsenic-endemic region. CONCLUSIONS. People residing in arsenic-endemic regions should be made aware of arsenic-related health hazards. Rainwater harvesting and good nutrition are the simplest measures which could be adopted by the exposed population in affected areas. Several methods have also been employed by governmental and non-government organizations to separate arsenic from contaminated water to combat arsenic-related diseases and carcinomas. COMPETING INTERESTS. The authors declare no competing financial interests.